1990
DOI: 10.1111/j.1476-5381.1990.tb12087.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into atropine‐induced antinociception

Abstract: 1 The effect of atropine on the nociceptive system was examined in mice and rats by use of the hot-plate, writhing and tail-flick tests. 2 Atropine dose-dependently produced analgesia, no effect and hyperalgesia. Analgesia was observed in both species with doses ranging from 1 to lOOug kg-while hyperalgesia was obtained with 5mg kg-3 Atropine antinociception was prevented by pirenzepine (0.1 ug per mouse, i.c.v.), dicyclomine (1Omg kg-1, i.p.), atropine-methylbromide (0.5 pg per mouse, i.c.v.) and hemicholiniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 18 publications
(18 reference statements)
2
38
2
Order By: Relevance
“…This is in agreement with the reported action of thioperamide as a histamine H3 receptor antagonist, and the antinociception observed might well be due to blockade of the H3 receptor and, consequently, to increased endogenous histamine release. This mechanism of action is not surprising if one bears in mind that two postsynaptic antagonists of the opioid and cholinergic systems naloxone and atropine, have also been demonstrated to induce antinociception when administered at low doses which are ineffective on the postsynaptic site, but which are capable of blocking the respective presynaptic receptors (Levine et al, 1979;Ghelardini et al, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…This is in agreement with the reported action of thioperamide as a histamine H3 receptor antagonist, and the antinociception observed might well be due to blockade of the H3 receptor and, consequently, to increased endogenous histamine release. This mechanism of action is not surprising if one bears in mind that two postsynaptic antagonists of the opioid and cholinergic systems naloxone and atropine, have also been demonstrated to induce antinociception when administered at low doses which are ineffective on the postsynaptic site, but which are capable of blocking the respective presynaptic receptors (Levine et al, 1979;Ghelardini et al, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…While caffeine, like all drugs interacting with presynaptic muscarinic auto- (Ghelardini et al 1990) and heteroreceptors , produces antinociception without any visible side effects, the direct muscarinic agonists and cholinesterase inhibitors provoke, at the same time, antinociception and a clear cholinergic symptomatology (tremors, sialorrhoea, diarrhoea, lacrimation etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…The doses and administration schedules of naloxone, CGP 35348, α-methyl-p-tyrosine and reserpine were suitable for preventing antinociception induced respectively by morphine (Ghelardini et al 1990), GABA B agonist baclofen (Malcangio et al 1991), amphetamine (Bartolini et al 1987) and the antidepressant drugs clomipramine and amitriptyline (Galeotti et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies (Ghelardini et al, 1990, it has been reported that atropine in animal experiments is either a cholinomimetic or a cholinolytic drug, depending on the dose. Very low doses of atropine which were inadequate for blocking muscarinic receptors (1-100 µg/kg in vivo; 10 -14 -10 -12…”
Section: Modes Of Actionmentioning
confidence: 96%